Effect of intranasal administration of Semliki Forest virus recombinant particles expressing interferon-beta on the progression of experimental autoimmune encephalomyelitis - Quinn, Kathrina (Trinity College (Dublin, Ireland). Department of Microbiology, 2006)
Multiple sclerosis (MS) is an autoimmune demyelinating disease of the CNS, characterized by the presence of sclerotic lesions throughout the brain. MS is thought to be a CD4+ T helper 1 disease caused by the infiltration of autoaggressive T cells which upregulate T helper-1 cytokines such as TNF-a and IFN-y. Much success has been achieved in the treatment of Relapsing Remitting Multiple Sclerosis (RRMS). It is thought that the antiproliferative activity of IFN-P may inhibit the expansion of the autoaggressive T cells in MS, therefore limiting disease progression.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin